2004
DOI: 10.1300/j081v18n02_03
|View full text |Cite
|
Sign up to set email alerts
|

Lighting Levels in the Dwellings of Homebound Older Adults

Abstract: Although poor lighting in the dwellings of older adults has been associated with falls, depression, and reduced visual performance, there has been little measurement of actual light levels in their homes. Knowing the interior light levels and preferences of older adults, especially the homebound, will be of value to service providers and designers in targeting effective interventions. This pilot study measured light levels in the apartments of 40 homebound older adults in New York City, and compared them with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 8 publications
3
36
0
1
Order By: Relevance
“…They found that conditions are too poor for proper vision. Similar results have been found and reported in the literature, for instance, in the United States by Hegde and Rhodes [10] and Bakker et al [11], and in Belgium by De Lepeleire et al [12]. In these studies, colour temperature of the light and its spectral composition were not considered, and three of the studies [10e12] did not consider vertical illuminances.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…They found that conditions are too poor for proper vision. Similar results have been found and reported in the literature, for instance, in the United States by Hegde and Rhodes [10] and Bakker et al [11], and in Belgium by De Lepeleire et al [12]. In these studies, colour temperature of the light and its spectral composition were not considered, and three of the studies [10e12] did not consider vertical illuminances.…”
Section: Introductionsupporting
confidence: 81%
“…This discrepancy, however, can be explained by inherent biases in satisfaction research among older adults [10]. Similar results have been found and reported in the literature, for instance, in the United States by Bakker et al [11], and in Belgium by De Lepeleire et al [12]. In these previous studies, colour temperature of the light and its spectral composition were not considered either, and the majority of studies did not consider vertical illuminances.…”
Section: Illuminances For Older Adultsmentioning
confidence: 61%
“…Field measurements of daytime residential light levels in both the USA and the Netherlands have found that the home-dwelling elderly rate their light levels as adequate even when they are considerably lower on average than recommendations based on visibility (Aarts & Westerlaken, 2005;Bakker, Iofel, & Lachs, 2004;Charness & Dijkstra, 1999). This is poignant when one considers that two field investigations have demonstrated improved quality of life in response to increased light levels in the homes of the elderly or partially sighted (Brunnström, Sörensen, Alsterstad, & Sjöstrand, 2004;Sorensen & Brunnstrom, 1995).…”
Section: Visual Systemmentioning
confidence: 99%
“…Bakker et al (2004) noted that for most people daylight was the principal light source, and yet many participants had their window shades drawn regardless of the time of day. They did not collect systematic information about the reason for this, but anecdotally reported that avoidance of uncomfortable visual contrast, avoidance of discomfort, privacy and thermal comfort were all cited as reasons for having shades drawn.…”
Section: Visual Systemmentioning
confidence: 99%
“…Despite the known benefits of lighting, older adults may not fully appreciate the role of lighting and rate home lighting as adequate when it is actually suboptimal (Bakker, Iofel, & Lachs, 2004). Moreover, improving lighting, contrast, and safety may be viewed by the client as less important than learning daily living skill strategies (Schuchard, Naseer, & de Castro, 1999).…”
Section: Benefits Of Optimal Lightingmentioning
confidence: 99%